Beyond the quantitative and qualitative divide: The salience of discourse in procedural justice policing research - Shon, Phillip C (Journal of criminology, 2021)
The dominant methods of studying police have involved quantitative analyses of surveys and systematic social observations of police behavior or qualitative methods such as ethnographies and interviews. The same trend applies to procedural justice research in policing. In prior works, the question of how police officers and citizens interact in situ is absent. We argue that procedural justice police research should move beyond the quantitative/qualitative distinction and consider other ways to collect and analyze data. We begin by providing a methodological critique of procedural justice research, and demonstrate the assumptions of discourse in extant works before we provide a blueprint for how to incorporate discourse analytic methods in the study of procedural justice and policing.